2017
DOI: 10.1037/ppm0000083
|View full text |Cite
|
Sign up to set email alerts
|

Violent video games increase voice stress: An experimental study.

Abstract: In most violent video games, players are put in stressful situations where enemies are trying to kill them. This is reflected by the results of previous research showing that violent video games increase physiological arousal (e.g., heart rate, blood pressure, galvanic skin response). In this study, I investigate the effect of playing violent video games on emotional stress detected by a new methodology: voice analysis. Because changes and disturbances in vocal responses can be understood as reactions to emoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
1
2
0
1
Order By: Relevance
“…Regarding the vocal aspects of players of digital games, an experimental study investigated the effect of playing violent games on emotional stress, detected by a new methodology: automated voice stress analysis. The results pointed out that violent digital games have physiological consequences among French players, especially men, thus confirming previous research that showed that violent digital games tend to increase physiological arousal (30) . Some elements of the present research should be observed for the interpretation of the results.…”
Section: Discussionsupporting
confidence: 88%
“…Regarding the vocal aspects of players of digital games, an experimental study investigated the effect of playing violent games on emotional stress, detected by a new methodology: automated voice stress analysis. The results pointed out that violent digital games have physiological consequences among French players, especially men, thus confirming previous research that showed that violent digital games tend to increase physiological arousal (30) . Some elements of the present research should be observed for the interpretation of the results.…”
Section: Discussionsupporting
confidence: 88%
“…In recent years, research has demonstrated an interest in the effects of video games on stress. Some research studies have found that video games induce stress (Hasan et al, 2013; Hasan, 2015; Ferguson et al, 2016), while others have shown that video games reduce or manage stress (Reinecke, 2009; Russoniello et al, 2009; Roy and Ferguson, 2016). Mixed findings may be a result of two limitations in current video game studies.…”
Section: Introductionmentioning
confidence: 99%
“…Additional research focused on the nature of video games has explored more deeply how violent games compared with non-aggressive ones can influence players' emotional responses. In a study by [66], it was found that playing violent games can trigger an increase in vocal stress compared with non-aggressive games. This observation is supported by research involving violent online games, which also demonstrated an increase in stress levels and the expression of tantrums.…”
Section: Discussionmentioning
confidence: 99%